OPTIMASI MASALAH TRANSPORTASI FUZZY MENGGUNAKAN METODE FUZZY MODIFIED DISTRIBUTION UNTUK MEMPREDIKSI BIAYA ANGKUTAN TOTAL DAN ALOKASI BARANG (PAKAN TERNAK) (Studi Kasus : CV. Mentari Nusantara Feedmill) - Ahmad Jufri; Akhmad Yusuf; Thresye Thresye (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2017)
Parameters in transportation problems include transport of cost, supply and demand not always ascertainable for sure and alterable over time. Because, uncertainty mentioned so can use fuzzy numbers. The use of fuzzy numbers on transport of costs, supply and demand resulted in the formation of fuzzy transportation problem. By using fuzzy transportation problem the total transport cost and commodity allocation can be predicted. Purpose of this study is to predict the total transport cost and commodity allocation. This study is a case study which collects data parameters from CV. Mentari Nusantara Feedmill. From the data research , obtained the initial solution total transport cost in February use Fuzzy North West Corner amounted Rp.33.136.709. And to determine the optimality of the initial solutions obtained use the Fuzzy Modied Distribution to obtain the total transport cost prediction in February amounted Rp.31.965.025. And also obtained the prediction allocation of commodity in February for Depo Cash Martapura amounted 6.192 kg, Depo Nalem Sembiring amounted 51.400 kg, Depo Siti Kamilah amounted 18.792 kg and Depo Tjou Tjie amounted 33.200 kg